Morphological Features of Spleen Tissue After Introduction of Fluorouracil and Cryopreserved Cord Blood Nucleated Cells - Kudokotseva, Olga V.; Volina, Viktoriya V.; Lomakin, Ivan I. (Problems of Cryobiology and Cryomedicine, 2016)
We studied the effect of administered cryopreserved nucleated cells of human cord blood (cCBNCs) on murine spleen tissue morphology under hemo- and immunosuppression induced by a single intraperitoneal injection of 5-fluorouracil (5-FU) antimetabolite of nucleic metabolism in the maximum tolerated dose. Progressing changes, typical for a damage caused by toxic substances, such as: congestion, exudation and leukocytes infiltration of spleen pulp; accumulation of macrophages either with phagocytized lymphocytes or their fragments; degenerative and necrotic changes in tissue elements of the pulp and follicles were revealed in spleen following 5‑FU introduction within entire observation period (16 days). A high degree of murine spleen reactivity in response to the administration of cryopreserved cord blood cells was found. To day 2 after cCBNCs administration we observed structural rearrangements in spleen, and already 10 days later 5-FU antimetabolite toxic injury the organ structure was back to the norm. Probl Cryobiol Cryomed 2016; 26(3): 249–258